DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI DI KABUPATEN KARANGANYAR - Umi Barokah; Dwidjono Hadi Darwanto; Supriyanto Supriyanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
The purpose of this research is to study the contribution of off-farm to income household and the effect of off-farm to income distribution between farm household. The location is choosen purposively based on the number of people as farmers, numbers and kind of industries and acessibility to reach economic centre. This research used multi stage sampling, the first was by cluster sampling, where all farm household from two village in Ngringo (kecamatan Jaten) and Tunggulrejo (kecamatan Jumantono) interviewed. And second stratified sampling based on farm size.The result showed that off-farm income (56,26 %) is greater than farm income (43,74 %). Off-farm income of small farmers (71,42 %) is greater than large farmers (45,18 %). Off-farm employment increased household income and the inequality of income tend to reduce. But off-farm employment is mainly for large farmers and close to the industrial area. In contrast, off-farm income increase inequality for small farmers in area far from industrial area